2006
DOI: 10.1115/1.2427074
|View full text |Cite
|
Sign up to set email alerts
|

Porous Medium Interconnector Effects on the Thermohydraulics of Near-Compact Heat Exchangers Treated as Porous Media

Abstract: A novel approach of treating near-compact heat exchangers (NCHX) (surface to volume ratio, α=100-300m2∕m3 with hydraulic diameter DM∼6mm) as a “global” porous media, whose thermohydraulic performance is being influenced by the presence of “local” tube-to-tube porous medium interconnectors, connecting the in-line arrangement of tubes (D=2mm) having square pitch of XT=XL=2.25, is investigated in this study using numerical methods. The thermohydraulics of the global porous media (NCHX) are characterized by studyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…This reduction can be attributed to the absence of the pressure drop penalty originally caused by the recirculation and vortices behind individual tubes in the inline configuration without the porous medium. A similar observation was made by Raju and Narasimhan (2007) in their numerical study of inline tube bank with porous interconnectors. In the present experimental study a maximum of 12 percent pressure drop reduction was observed for the range of flow considered.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…This reduction can be attributed to the absence of the pressure drop penalty originally caused by the recirculation and vortices behind individual tubes in the inline configuration without the porous medium. A similar observation was made by Raju and Narasimhan (2007) in their numerical study of inline tube bank with porous interconnectors. In the present experimental study a maximum of 12 percent pressure drop reduction was observed for the range of flow considered.…”
Section: Resultssupporting
confidence: 81%
“…1a is considered for numerical simulation, initially without contact resistance between tubes and porous interconnectors and later by introducing thermal contact resistance. A commercially available CFD software is used for the simulations The numerical procedure followed here is similar to that detailed in Raju and Narasimhan (2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They pointed out important reasons that negate a direct comparison between the numerical and experimental results. Raju and Narasimhan [10], using a numerical study, presented a novel approach of treating near compact heat exchangers (in-line tube to tube arrangement) as global porous media for estimating the global thermo-hydraulic characteristics. The authors presented correlations for nondimensional pressure drop and Nusselt number for characterizing the thermo-hydraulic performance of the chosen near compact heat exchanger configurations.…”
Section: Introductionmentioning
confidence: 99%